2021
DOI: 10.1007/s11356-021-17640-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the EU emissions trading system help reduce PM2.5 damage? A research based on PSM-DID method

Abstract: Air quality, especially haze pollution, has become an important issue that threatens the sustainable development and health of human beings. To study and formulate effective environmental regulations to control and reduce the concentration of PM 2.5 in the air, especially to clarify the effect of the relevant emission trading system on the emission reduction of air pollutants is a research topic with important practical signi cance and theoretical value. Previous studies on the environmental effects of emissio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Generally, market-based environmental regulation policies adopt a point-to-point strategy, that is, a “region-city” hierarchical strategy. The macro factors that affect the implementation of the pilot policies for emission trading in the pilot areas include the degree of economic development at the regional level and the degree of improvement of environmental protection policies (Coleman et al, 2019; Porter & Linde, 1995; Si & Cao, 2021; Wan et al, 2022; Wei & Zhenxing, 2021). Since the implementation of emission trading policies on regional industry resource allocation efficiency may be related to the previous economic and environmental development level of these areas, in this case, the implementation of the emission trading policy cannot be regarded entirely as an exogenous impact on the efficiency of resource allocation of local enterprises.…”
Section: Empirical Process and Results Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, market-based environmental regulation policies adopt a point-to-point strategy, that is, a “region-city” hierarchical strategy. The macro factors that affect the implementation of the pilot policies for emission trading in the pilot areas include the degree of economic development at the regional level and the degree of improvement of environmental protection policies (Coleman et al, 2019; Porter & Linde, 1995; Si & Cao, 2021; Wan et al, 2022; Wei & Zhenxing, 2021). Since the implementation of emission trading policies on regional industry resource allocation efficiency may be related to the previous economic and environmental development level of these areas, in this case, the implementation of the emission trading policy cannot be regarded entirely as an exogenous impact on the efficiency of resource allocation of local enterprises.…”
Section: Empirical Process and Results Analysismentioning
confidence: 99%
“…In addition to the internal role, the mutual influence of external industry resource allocation efficiency should also be considered. Implementing market-oriented environmental regulation policies will cause enterprises affected by financing constraints to be unable to maximize their production efficiency to obtain sufficient emission trading resources, resulting in a mismatch of enterprise resource structure (Wan et al, 2022). The market-oriented environmental regulation policy will affect the resource allocation efficiency of enterprises through market regulation of emission trading resources and government administrative supervision constraints.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…This often includes the role played by the digital economy, the development of cities known for their innovation, and the impact of environmental policies [60,61]. Comparative studies highlight that the European Union's methods for addressing climatic alterations often involve fiscal tools, such as carbon emissions trading system [32], which leverage the market's inherent tendency towards self-regulation with the aim of fostering energy saving and reducing emissions. Meanwhile, the strategy adopted by China, which is similar to those put in place in South Korea and the United States, leans towards instigating incentives or environmental legislation [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Combating climate change is a gradual, phased and long-term international challenge, and many countries and regions have adopted corresponding measures to achieve the goals of reducing energy use and lowering emissions. In studying of other countries, Wang et al [32] use the PSM-DID method to select PM2.5 hazard data and related information from 147 countries listed in the World Development Index, and investigate if the European Union Emissions Trading System has a spillover effect on PM2.5 emission reductions. The study found that the European Union Emissions Trading System does not only promote a reduction in PM2.5 damage but also dynamically affects PM2.5 emission reduction during different stages of implementation.…”
Section: Research Methodological Aspectsmentioning
confidence: 99%
“…With growing public concern regarding global warming, research on the carbon emissions trading market has been productive, and a systematic review of the literature shows that, as a kind of environmental regulation, the carbon emissions trading policy has received significant attention from scholars in recent years. There is a large portion of literature regarding the emission reduction performance of carbon trading, and scholars have generally agreed that the carbon trading mechanism has contributed greatly to environmental improvement in terms of reducing carbon emissions and reducing carbon intensity [ 37 , 38 , 39 , 40 , 41 , 42 ]. National carbon emissions trading policies are effective in recovering GDP losses [ 43 ], and there are return and volatility spillovers among the pilot regions [ 44 ].…”
Section: Literature Reviewmentioning
confidence: 99%